Assessment of COVID-19 vaccination refusal among healthcare workers in Ethiopia - Berhe, Elsa Tesfa; Shama, Adisu Tafari; Ahmed, Mohammed Musa; Gesesew, Hailay Abrha; Ward, Paul R.; Gebremeskel, Teferi Gebru (Frontiers in Public Health, 2022)
Background: Even though the emerging of the COVID-19 vaccine and the increasing vaccination rate is promising, there are reports of refusal to get vaccinated in a different segment of the population including health care workers. Objective: This study determines the acceptance/refusal of the COVID-19 vaccination and its predictors among health care workers in Ethiopia. Methods: A cross-sectional survey was conducted among a group of health care workers at different health facilities in Ethiopia. Data were collected from 1 to 30th of July 2020. Data were collected from 403 participants through an online Google submission form. Data were entered into Epi-info 7 and exported to SPSS version 20 for analysis. Results: 38.5% of the health care workers in the study had refused COVID-19 vaccination. Younger age groups versus 40 and above years (age 20-24 year [AOR: 0.03, 95% CI (0.00, 0.48)], age 25-29 year [AOR: 0.02, 95% CI (0.00, 0.49)] and age 30-34 year[AOR: 0.04 (0.00, 0.49)]] and Medical Doctors versus Nurses [AOR: 0.06, 95% CI, (0.01, 0.42)] were reported as risk factors; and working in academic staff vs hospital [AOR: 4.42, 95% CI (1.85, 10.54)] was reported as a protective factor towards refusal of COVID-19 vaccination. Conclusion: Two-fifths of health care workers in Ethiopia indicated refusing of COVID-19 vaccination, implying a significant barrier to achieving WHO's a target of 70% double vaccination rate in mid-2022.